63.0k views
4 votes
HELP FAST. I NEED THIS ANSWER FAST

HELP FAST. I NEED THIS ANSWER FAST-example-1
User Mewel
by
5.2k points

2 Answers

4 votes

Answer:

First find the cubes and squares of the 1st and 2nd expression.

1st expression ⇒
(-(2)/(3) x^2y)^3 = -(8)/(27)x^6y^3

2nd expression ⇒
(-(3)/(4)xy^2)^2 = -(9)/(16)xy^4

Now you all you need to do is multiply the 1st expression to 2nd expression.


-(8)/(27)x^6y^3*-(9)/(16)xy^4\\\\= (72)/(432) x^7y^7

User Amit Prakash
by
5.1k points
2 votes

Answer:

abunda la caca

( its 10m*9y)

Explanation:

User Jignesh Fadadu
by
5.4k points